The Influence of Accounting Systems and Information Systems on the Village Development Index : (a Study in Villages in Central Sulawesi Province) - Abdilah Rifa'i Latif; Andi Chairil Furqan; Femilia Zahra; Muhammad Din; Rasyid Muhammad Hartoyo; Stevin David (International Journal of Economics, Management and Accounting, 2025)
By measuring the village development index, this study aims to determine how accounting and information systems affect village development. The village development index comprises of three measurements, specifically the social, financial  and environmental resilience index. Utilizing quantitative strategies and cross-sectional data from 1,842 towns in Central Sulawesi territory in 2021. The study's conclusions demonstrate that while the information system significantly influences village development, the accounting system has no impact on village development. These findings show that the use of information and communication innovation has an impact on village improvement. This disclosure found that cell phones have an impact on village development including social, financial and environmental and internet signals have an influence on village development including economic and social but not the environment.